RETIREES’ PSYCHOLOGICAL STRUGGLES IN ERNEST HEMINGWAY’S THE OLD MAN AND THE SEA - Bertova Simanihuruk; Rini Rutcahyati Manalu (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study explores and analyzes the psychological struggles of retirees as portrayed in Ernest Hemingway's novel The Old Man and the Sea. The research uses a qualitative method with a psychosocial theory approach. The data are collected through comprehensive reading and identifying relevant narrative, dialogue, and symbolic elements. The data are analyzed using Miles and Huberman’s method, which includes data collection, data reduction, data display, and conclusion drawing. The novel is viewed as a reflection of various psychological struggles, such as identity crisis, fear of uselessness, and loneliness. The results show that identity crisis is represented through Santiago’s self-doubt after failing to catch fish for many days. He feels that he is no longer the great fisherman he once was. The fear of uselessness is shown through his physical weakness and the fact that he is no longer as strong as he was in his youth. Nevertheless, he continues to fight hard to prove that he is still useful and that his life still has meaning. Loneliness is illustrated by his solitary life: no wife, no children, and no close friends. In conclusion, the author wants to convey that people do not need to run away from the reality of growing old. Instead, they should accept it wholeheartedly and continue to live their old age with enthusiasm, meaning, and happiness.